Endo/exothermic chemical processes influences of tri-hybridity nanofluids flowing over wedge with convective boundary constraints and activation energy. - Sajid, Tanveer (2023)
Prandtl Eyring fluid and stretchable wedge have multiple usages in many industries. The present study aims to investigate the impact of modified Buongiorno trihybrid nanofluid on Prandtl Eyring fluid past a wedge with the addition of various influences like endothermic/exothermic reactions, thermal radiation, and thermal conductivity, Cattaneo-Christov double diffusion. Aluminium alloys (AA7072), Aluminium alloys (AA7075) and Silver (Ag) are used as nanocomponents. Prandtl Eyring fluid is employed as a conventional liquid in the preparation of nanofluids by blending nano components into the base fluid. Further, the flow model is imposed with Modified Buongiorno nanofluid. By using the similarity approach, the proposed mathematical flow model of partial differential equations (PDEs) is turned into highly nonlinear ordinary differential equations (ODEs). Throughout the whole range of material parameters, the solution for the ensuing nonlinear boundary value issue is given by employing the finite element method (FEM). The numerical results of Prandtl Eyring ternary HNF motion, thermal and solute profiles are performed through graphical amassment on the collected data and discussed in detail. The numerical significances of material sections, such as the frictional force, local Nusselt quantity, and local Sherwood number requirements, are supplied in tabular form. Further, it also presents the validation and performance characteristics of the proposed device with previously published work and found excellent accuracy. In comparison to hybrid nanoparticles, the consequences reveal that heat transmission is amplified in the case of tri-hybrid nanoparticles. The numerical consequences show that the heat transfer amount reduces in the situation of exothermic reactions parameter Ω < 1 and rises due to magnification in the status of endothermic reactions parameter Ω > 1.